Impact of Outer Shell Structure and Localization Effects on Charge Carrier Dynamics in GaAs/(In, Ga)As Nanowire Core–Shell Quantum Wells. Issue 5 (7th February 2019) - Küpers, Hanno; Corfdir, Pierre; Lewis, Ryan B.; Flissikowski, Timur; Tahraoui, Abbes; Grahn, Holger T.; Brandt, Oliver; Geelhaar, Lutz
Abstract : Herein, the charge carrier dynamics in GaAs/(In, Ga)As/(Al, Ga)As core–shell nanowires with different outer shell structures are studied. Localization of charge carriers in the minima of potential fluctuations is shown to govern the recombination processes at low temperatures. At higher temperatures, thermionic emission of carriers from the (In, Ga)As shell quantum well leads to a decrease of the luminescence efficiency for a sample with a GaAs outer shell. This effect can be reduced by introducing an AlAs barrier shell. However, the interfaces to this barrier act as an additional source for nonradiative recombination. These results will help in achieving high luminescence intensities at room temperature of light‐emitting devices based on nanowire shell quantum wells. Abstract : Different nanowire core–shell structures incorporating (In, Ga)As shell quantum wells are investigated with respect to their luminescence properties. It is shown that AlAs barrier shells are necessary to achieve high room‐temperature luminescence intensities. Nonetheless, the interface quality of the quantum well is crucial for achieving high overall intensities and a suitable solution using a spacer shell is presented.